Digital Literacy as a Bridge of Social Exclusion Postcovid-19 (Docentes 2.0 Journal, 2021)
A new window of the 21st century begins and with it a time of profound social challenges and it is how to continue integrating Information and Communication Technologies (ICT) and multiple technological innovations to daily activities. The world today has a great challenge due to the impact of COVID-19, new opportunities arise in the field of technological skills, giving rise to new inequalities and social gaps, which motivates the creation of new useful strategies to be able to address them. The present study aimed to strengthen digital-technological abilities and skills in infocommunication environments for the development of collaborative work. In the development of the research, the mixed approach was used, and the questionnaire and survey were used in the information gathering process. The population under study was made up of 130 Community Educational Agents, between 25 and 68 years old, belonging to the Cooperativa de Multiactiva de Agentes Educativas de Girón COOMUDAEG, located in Girón Santander, Colombia. The findings conclude that in post-COVID-19-time, Educational Agents can continue strengthening their skills and technological skills in infocommunication environments, to strengthen collaborative work, problem solving in their daily and professional lives, thus reducing the risk of exclusion. Social.
Keywords: Digital literacy; technological skills; social exclusion